Penerjemahan Semantis Dan Borrowing Pada Teks Explanasi COP27: Climate Chaos’ Warning AS UN Summit Begins - Halimah, Santi Nur; Pendit, Ni Putu Meri Dewi (LP2M, 2023)
The study discusses about translation techniques used in news articles and analyzes the techniques to be used in translating the article entitled